Preterm feeding recommendations are achievable in large-scale research studies. Issue 1 (December 2016) - Cheikh Ismail, Leila; Giuliani, Francesca; Bhat, Bashir; Bishop, Deborah; Papageorghiou, Aris; Ochieng, Roseline; Puglia, Fabien; Altman, Douglas; Maia-Schlüssel, Michael; Noble, Julia; Bertino, Enrico; Gravett, Michael; et al.
Abstract Background The INTERGROWTH-21st Project aimed to produce international, prescriptive, postnatal growth standards for preterm infants born to healthy, well-nourished mothers receiving adequate antenatal care. There is little information available regarding optimal postnatal growth among uncomplicated preterm newborns. We describe how the preterm infants contributing to the standards followed evidence-based feeding recommendations. Methods In the Fetal Growth Longitudinal Study (FGLS), a component of the INTERGROWTH-21st Project, fetal growth was monitored by ultrasound from <14 weeks' gestation until birth in pregnancies at low risk of adverse outcomes. All preterms (≥26+0 and <37+0 weeks' gestation) were followed up during infancy. Internationally-accepted feeding recommendations for preterms, agreed by the INTERGROWTH-21st Neonatal Group, were implemented at each study site. Standardised questionnaires served to record information on their feeding practices. Results Feeding data were collected from 201 eligible preterms. The median (interquartile range, IQR) gestational age at birth was 36.0 (35.0 – 36.6) weeks. The prevalence ofany breastfeeding was 82 % within 72 h of birth, 96 % at 2 weeks, 82 % at 4 months and 70 % at 8 months postnatal age. The figures forexclusive breastfeeding were 51 % within 72 h of birth, 72 % at hospital discharge, 49 % at 4 months, 38 % at 5 months and 12 % at 6 months. Complementary foods were introduced at a median (IQR) postnatal age of 6.0 (5.1 – 6.8) months. Conclusion Most preterms were exclusively breastfed upon hospital discharge, and breastfeeding remained a substantial source of nutrition throughout the study. Recommendations, centred on breastfeeding, were adequately followed within the expected variation of such diverse settings.